ANALISIS PENGARUH BRAND IMAGE, BRAND TRUST DAN ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN (Survei pada Konsumen Skincare Larissa Aesthetic Center Surakarta) - Dewi, Riska Sartika; Suprayitno, Marjam Desma Rahadhini & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2018)
The purpose of this study is to analyze the significance of the influence of brand image, brand trust, and product attribute to purchasing decisions. The type of this research is survey on consumer Skincare Larissa Aesthetic Center Surakarta Jl. Gajah Mada No. 103 Surakarta. Typpes data use qualitative data and quantitative data. Data sources use primary data sources and secondary data. The population of the research is all consumer Skincare Larissa Aesthetic Center Surakarta with a sample of 100 people with sampling technique accidental sampling. Data collection techniques user questionnaires and documentation. Data analysis techniques use instrument test, classical assumption test, descriptive statistical analysis, multiple linear regression, t test, F test, and coefficient of determination. The result showed that brand image has a significant efect on purchasing decisions, brand trust is not have a significant effect on purchasing decisions and product attributes have a significant effect on purchasing decisions.Keywords: brand image, brand trust, product attribute, purchasing decisions.